The determinants of housework time - Leslie S. Stratton (IZA World of Labor, 2020)
The time household members in industrialized countries spend on housework and shopping is substantial, amounting to about half as much as is spent on paid employment. Women bear the brunt of this burden, driven in part by the gender wage differential. Efforts to reduce the gender wage gap and alter gendered norms of behavior should reduce the gender bias in household production time and reduce inefficiency in home production. Policymakers should also note the impact of tax policy on housework time and its market substitutes, and consider ways to reduce the distortions caused by sales and income taxes.
Keywords: D13; J22; J16; H31; J10; 330; housework; gender; home production; tax policy; outsourcing